Jaw muscle reconstruction of the late Pliocene Psittaciform Nandayus vorohuensis from Argentina - Carril, Julieta (2014)
The aim of this contribution is to verify the presence of the suborbital arch and the ethmomandibularis and pseudomasseter muscles in the holotype of Nandayus vorohuensis (Tonni and Noriega, 1996) in order to gain a better understanding of the capabilities of its cranio-mandibular complex and provide new tools for the discussion on the evolution of these unique structures. These apomorphies enables Psittaciformes to exert strong bite forces. Muscle reconstruction was performed based on the presence of muscle attachment scars and on the basis of the jaw-muscle descriptions of the extant Myiopsitta. Our results indicate that the suborbital arch is absent and the ethmomandibularis and the pseudomasseter muscles were present. This condition is shared with the extant Neotropical Pionites and Myiopsitta, so we assume that their trophic habits are similar. The heterogeneous distribution of these characters reaffirms the idea that the direction of the evolutionary changes may have varied independently in the crown group Psittaciformes more than once.